Optimization of Regional Property Reporting Based on Simda Application at the Education and Culture Office in West Sumbawa Regency - Nurdin, Nurdin; Suparman, Suparman; Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research focuses on optimizing the reporting of regional property through the implementation of the SIMDA application at the West Sumbawa Regency Education and Culture Office. A qualitative method with an interpretive descriptive approach was used, involving seven informants who were interviewed as the main data source. The data collection instrument chosen is an interview, while data analysis is carried out through data reduction and data presentation. Optimization of reporting through the SIMDA application at the Education and Culture Office is expected to provide a number of benefits, such as real-time monitoring of asset and inventory status, increasing data accuracy by reducing human error, operational efficiency in saving time and reducing administrative complexity, as well as increased transparency and accountability in asset management. In addition, data integration with other systems, asset depreciation monitoring, and guaranteed data security are additional advantages of this application. The conclusions of this study indicate that the optimization of SIMDA Application-Based Regional Property Reporting at the Education and Culture Office in West Sumbawa Regency has proven to be very effective. The research recommendations highlight the need for improvements in various items in the SIMDA application in order to better meet the needs and challenges of asset reporting within local government.